Getting the right spin: A theory of optimal viral marketing - Pier-André Bouchard St-Amant (Queen's University, Department of Economics, 2012)
I develop a theoretical framework for studying viral communications through a principal agent set-up. The principal derives wealth from a signal in a society while agents in the society talk to each other. A society is likely to create a viral bubble if there is a short loop of positive reinforcement of the message. The principal is more likely to use widespread marketing strategies with a weaker effect if she is impatient. She will however prefer a viral communication strategy with stronger effects if she is patient. Such framework can be used to derive an optimal solution computable in polynomial time. All in all, the model suggests principals have incentives to generate spins and that the way information is spread matters in transitionary dynamics of an economy.
Keywords: D83; D85; 330; Network Theory; Viral Marketing; Principal Agent